Density Functional Prediction of Quasiparticle, Excitation, and Resonance Energies of Molecules With a Global Scaling Correction Approach - Yang, Xiaolong; Zheng, Xiao; Yang, Weitao (Frontiers in Chemistry, 2020)
Molecular quasiparticle and excitation energies determine essentially the spectral characteristics measured in various spectroscopic experiments. Accurate prediction of these energies has been rather challenging for ground-state density functional methods, because the commonly adopted density function approximations suffer from delocalization error. In this work, by presuming a quantitative correspondence between the quasiparticle energies and the generalized Kohn-Sham orbital energies, and employing a previously developed global scaling correction approach, we achieve substantially improved prediction of molecular quasiparticle and excitation energies. In addition, we also extend our previous study on temporary anions in resonant states which are associated with negative molecular electron affinities. The proposed approach does not require any explicit self-consistent-field calculation on the excited-state species, and is thus highly efficient and convenient for practical purposes.